Testosterone, oxytocin and co-operation: A hypothesis for the origin and function of music - Fukui, Hajime; Toyoshima, Kumiko (Frontiers in Psychology, 2023)
Since the time of Darwin, theories have been proposed on the origin and functions of music; however, the subject remains enigmatic. The literature shows that music is closely related to important human behaviours and abilities, namely, cognition, emotion, reward and sociality (co-operation, entrainment, empathy and altruism). Notably, studies have deduced that these behaviours are closely related to testosterone (T) and oxytocin (OXT). The association of music with important human behaviours and neurochemicals is closely related to the understanding of reproductive and social behaviours being unclear. In this paper, we describe the endocrinological functions of human social and musical behaviour and demonstrate its relationship to T and OXT. We then hypothesised that the emergence of music is associated with behavioural adaptations and emerged as humans socialised to ensure survival. Moreover, the proximal factor in the emergence of music is behavioural control (social tolerance) through the regulation of T and OXT, and the ultimate factor is group survival through co-operation. The ‘survival value’ of music has rarely been approached from the perspective of musical behavioural endocrinology. This paper provides a new perspective on the origin and functions of music.